Isolation, sequencing and expression of the gene encoding acetoacetyl-coa thiolase from Panax vietnamensis Ha et Grushv. - Trinh, Vu Thi; Han Ly, Luu; Hue, Huynh Thi Thu; Thu Hien, Le Thi (Vietnam Journal of Biotechnology, 2021)
Panax vietnamensis Ha et Grushv., naturally distributed in Ngoc Linh Mountain, is an endemic Panax species of Vietnam. For centuries, P. vietnamensis has been used in traditional folk medicine to treat many serious diseases or enhance physical strength. Ginsenosides are responsible for most of the medicinal effects of the Panax species. Acetoacetyl-CoA thiolase (AACT) is considered as an important enzyme involved in the biosynthesis of ginsenoside. In this study, a full-length cDNA of the gene encoding AACT protein (GeneBank accession number MZ272018) was obtained from P. vietnamensis using reverse transcription PCR. The gene open reading frame (1224 bp) encodes 408 amino acids. This cDNA sequence is 99.08% similar to the cDNA sequence of Panax notoginseng (KJ804173.1). The functional analysis of its protein by InterPro showed that the structure of AACT monomer consists of three domains, including thiolase-like domain (17-285), N-terminal (18-276), and C-terminal (286-406). Although there were some differences in the nucleotide sequence of the AACT cDNA gene between P. vietnamensis and the reference species, all important domains and sites related to the thiolase activity were observed. Phylogenetic analysis using AACT cDNA gene sequence revealed a close relationship of P. vietnamensis with P. notoginseng and Trachyspemum ammi. The quantitative real-time PCR results indicated the expression of AACT gene of P. vietnamensis depended on types of tissue and plant developmental stages (1, 4, 6 and 11 years old). The gene was expressed at higher levels in roots than in leaves and the highest expression of AACT gene was detected in the 11-year-old roots. The results provided valuable information for further studies on the biosynthesis of ginsenoside in P. vietnamensis in particular and Panax species in general.